2011
DOI: 10.1038/mt.2010.312
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Expression From Oncolytic Vaccinia Virus Enhances Vaccine Therapies of Cancer

Abstract: Tumor vaccines can induce robust immune responses targeting tumor antigens in the clinic, but antitumor effects have been disappointing. One reason for this is ineffective tumor infiltration of the cytotoxic T lymphocytes (CTLs) produced. Oncolytic viruses are capable of selectively replicating within tumor tissue and can induce a strong immune response. We therefore sought to determine whether these therapies could be rationally combined such that modulation of the tumor microenvironment by the viral therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 36 publications
0
99
0
1
Order By: Relevance
“…There is also additional evidence that tumors infected with OVs can trigger danger signals by dendritic cells and promote cross-antigen presentation, ultimately leading to the elicitation of innate and adaptive immune responses(42). Thus, the positive effects of armed OVs observed in our own and other models(36, 43) may be further amplified in patients due to the recruitment of other components of the immune system.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…There is also additional evidence that tumors infected with OVs can trigger danger signals by dendritic cells and promote cross-antigen presentation, ultimately leading to the elicitation of innate and adaptive immune responses(42). Thus, the positive effects of armed OVs observed in our own and other models(36, 43) may be further amplified in patients due to the recruitment of other components of the immune system.…”
Section: Discussionmentioning
confidence: 58%
“…While we and others have previously focused on identifying chemokines specifically produced by tumor cells and on engineering CAR-T cells with the cognate receptor(2022), here we selected RANTES as a broadly applicable chemokine because its receptors CCR1, CCR3, and CCR5 are retained by ex vivo expanded T cells(22, 36). This assures that upon adoptive transfer T cells will migrate to multiple types of tumors if they are forced to release RANTES.…”
Section: Discussionmentioning
confidence: 99%
“…is a known cytokine serving as an autocrine or paracrine growth factor for tumor and stromal cells, and is a mediator of the complex networks existing between tumor cells and the stromal microenvironment (27)(28)(29)(30). However, the molecular mechanism underlying this cellular event remains (2)) or scramble (Scr) shRNA control in the presence or absence of the GLI2 expression construct.…”
Section: Ccl5 Modulates Il-6 Expression and Secretion In Wm Stromal Cmentioning
confidence: 99%
“…Kirn et al reported protective immunity following tumor eradication with an oncolytic vaccinia virus expressing interferon-b in an immunocompetent tumor model, and that animals were refractory to subsequent tumor challenge [49]. In addition, Li et al reported that expression of the chemokine Chemokine (C-C motif) ligand 5 (regulated on activation, normal T cell expressed and secreted; RANTES) resulted in increased lymphocyte chemotaxis to tumors and increased efficacy when compared to the parental vvDD vector [50].…”
Section: Support For Immunotherapeutic Potential Of Oncolytic Vaccinimentioning
confidence: 97%